Formalization of versioning rules for XML schema using UML class diagram - Aman, Hananni; Ibrahim, Rosziati (Little Lion Scientific, 2017)
In agile software development methodology, XML schema is used for developing the web applications. The major problem in using the agile software development methodology is capturing the software requirements especially when versioning occurred in XML Schema. This paper presents how to capture software requirements for document changes when versioning occurred in XML Schema. UML Class Diagram is used in addressing the versioning rules. Once the versioning rules are captured, these rules are then being formalized for better understanding of the versioning problem occurred in XML Schema.